Exploring the Molecular Structure of Imidazolium–Silica‐Based Nanoparticle Networks by Combining Solid‐State NMR Spectroscopy and First‐Principles Calculations. Issue 46 (21st September 2014) - Neouze, Marie‐Alexandra; Kronstein, Martin; Litschauer, Marco; Puchberger, Michael; Coelho, Cristina; Bonhomme, Christian; Gervais, Christel; Tielens, Frederik
Abstract A DFT‐based molecular model for imidazolium–silica‐based nanoparticle networks (INNs) is presented. The INNs were synthesized and characterized by using small‐angle X‐ray scattering (SAXS), NMR spectroscopy, and theoretical ab initio calculations. 11B and 31P HETCOR CP MAS experiments were recorded. Calculated 19F NMR spectroscopy results, combined with the calculated anion–imidazolium (IM) distances, predicted the IM chain density in the INN, which was also confirmed from thermogravimetric analysis/mass spectrometry results. The presence of water molecules trapped between the nanoparticles is also suggested. First considerations on possible π–π stacking between the IM rings are presented. The predicted electronic properties confirm the photoluminescence emissions in the correct spectral domain.